Kombinasi Isometric Handgrip dan Pursed Lips Breathing dalam Menurunkan Tekanan Darah Pasien Hipertensi: Case Report - Moh. Nur Cahyo Firdaus; Anis Ika Nur Rohmah (Holistic Nursing and Health Science, 2025)
AbstractHypertension is a global health problem that requires pharmacological and non-pharmacological treatment. A combination of non-pharmacological interventions such as isometric handgrip and pursed lips breathing has the potential to have synergistic effects in lowering blood pressure, but there is still little evidence evaluating both intervention simultaneously during several days. This study aims to evaluate the effectiveness of the combination of isometric handgrip and pursed lips breathing in lowering blood pressure in hypertensive patients during five days. This study used a case study design with two female respondents aged 53 and 65 years who suffered from 1st and 2nd degree hypertension. The intervention was carried out for 5 days with one daily session directly supervised by the researcher. Isometric handgrip and pursed lips breathing are done alternately in the same session. Blood pressure was measured before and after the intervention. The results showed a decrease in blood pressure in both respondents. Systolic blood pressure decreased by 30 mmHg and diastolic decreased by 15  mmHg after 5 days of intervention. Respondents also reported feeling more relaxed and comfortable. The combination of isometric handgrip and pursed lips breathing is effective in lowering blood pressure in hypertensive patients. This intervention can be used as an easy, cheap, and safe nurse self-therapy to support hypertension control in the community. Future experimental studies are required to examine the effect of intervention in larger populations.Keywords: Isometric Handgrip; Pursed Lips Breathing; HypertensionAbstrakHipertensi merupakan masalah kesehatan global yang memerlukan penanganan farmakologis dan non-farmakologis. Kombinasi intervensi non-farmakologis seperti isometric handgrip dan pursed lips breathing berpotensi memberikan efek sinergis dalam menurunkan tekanan darah, namun masih sedikit bukti yang mengevaluasi keduanya secara bersamaan beberapa hari berturut-turut. Penelitian ini bertujuan untuk mengevaluasi efektivitas kombinasi isometric handgrip dan pursed lips breathing dalam menurunkan tekanan darah pada pasien hipertensi selama lima hari. Penelitian ini menggunakan desain case report dengan dua responden perempuan berusia 53 dan 65 tahun yang menderita hipertensi derajat 1 dan 2. Intervensi dilakukan selama 5 hari dengan satu sesi harian yang diawasi langsung oleh peneliti. Isometric handgrip dan pursed lips breathing dilakukan secara bergantian dalam satu sesi yang sama. Tekanan darah diukur sebelum dan setelah intervensi. Hasil menunjukan penurunan tekanan darah pada kedua responden. Tekanan darah sistolik turun 30 mmHg dan diastolik turun 15 mmHg setelah 5 hari intervensi. Responden juga melaporkan perasaan lebih rileks dan nyaman. Kombinasi isometric handgrip dan pursed lips breathing efektif menurunkan tekanan darah pada pasien hipertensi. Intervensi ini dapat dijadikan sebagai terapi mandiri perawat yang mudah, murah, dan aman untuk mendukung pengendalian hipertensi di komunitas. Penelitian eskperimen lanjutan dibutuhkan untuk menguji efektivitas pada skala populasi yang lebih luas.Kata kunci: Isometric Handgrip; Pursed Lips Breathing; Hipertensi